A Memória não se rende: exílio, testemunho e sobrevivência em Herbert Daniel, Mónica Echeverría e Carmen Castillo - Evandro Figueiredo Candido (2023)
This research is based on Passagem para o próximo Sonho (1982), by Herbert Daniel , and Santiago-París: el vuelo de la memoria (2002a; 2002b), by Mónica Echeverría and Carmen Castillo. Both refer to Brazilian and Chilean dictatorships, respectively in the 60s and 70s. The main objective is to study the memory, the testimony and survival in both exile and post-exile. In order to develop this research, we organized this text in five chapters. The first chapter studies Passagem para o próximo Sonho, considering the exile and its several aspects. It highlights Herbert Daniel’s trajectory, since the days of clandestinity, going through his exile in Paris, up to his difficult return, that also points to a troubled democratic transition in Brazil. Considering this approach, the chapter uses the following references: Edward Said (2003); Denise Rollemberg (1999); Georges Didi-Huberman (2014); James Green (2018); and Paul Ricœur (2007). The second chapter, based on Santiago-París: el vuelo de la memoria, focus on the experiences, challenges and daily resistances of Mónica Echeverría e Carmen Castillo since the childhood up to the adulthood, in a life path in which they should figure as “queens of the house”. Contributions from Judith Butler (2012), Guacira Lopes Louro (2008), Richard Miskolci (2013), Tania Swain (2001), Marilda Ionta (2004), Mary del Priori (2011) and Fernando Ainsa (1997) were important for the dialog between the approached subjects and the theoretical and critical perspectives about them. The following chapter analyzes the context of the military coup in Chile and the implementation of the Chilean dictatorship. It studies Mónica Echeverría and Carmen Castillo's resistance strategies and their contributions in the scope of clandestinity. Heraldo Muñoz (2010); José Maria Rabêlo (2001); Darcy Ribeiro (2012), além de Grínor Rojo (2016) e Susel Oliveira da Rosa (2013) were important to clarify the paths followed in this thesis. In the fourth chapter, we focus on Mónica Echeverría and Carmen Castillo 's path out of Chile and their difficult returns, marked by the country' s changes due to the dictatorial regime. In order to understand the post-exile scenario, and the persistence of the testimony, to construct a democracy, the authors: Didi-Huberman (2002), Beatriz Sarlo (2006), Márcio Seligmann-Silva (2003) and Jeanne Marie Gagnebin (2003) were important. The final chapter confronts the narratives, aiming to promote a dialog between these memories and to reflect about reinterpretations of history. For this section, we regard aspects such as: heterogeneity of exile, the solitude, the difficult returns, as well as the author’s views about politics and resistance.